2018
DOI: 10.1002/term.2781
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of fluorescent nanoparticle‐labeled bone marrow mesenchymal stem cells in vitro and after intra‐articular injection

Abstract: Mesenchymal stem cells (MSCs) improve the osteoarthritis condition, but the fate of MSCs after intra-articular injection is unclear. We used fluorescent nanoparticles (quantum dots [QDs]) to track equine MSCs (QD-labelled MSCs [QD-MSCs]) in vivo after intra-articular injection into normal and osteoarthritic joints. One week after injection of QD-MSCs, unlabelled MSCs, or vehicle, we determined the presence of QD-MSCs in synovium and articular cartilage histologically. In vitro, we evaluated the persistence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In a previous study, we reported no adverse effects of CdSe/ZnS QD labeling on the differentiation potential of adult stem cells isolated from rat pancreas [9]. Similar observations for other stem cell types such as embryonic stem cells, induced pluripotent stem cells or mesenchymal ones have recently been published [10][11][12]. Intriguingly, others have noted changes in the differentiation profile of stem cells after labeling with nanoparticles such as the inhibition of osteogenesis with QD labeled bone marrow mesenchymal stem cells [13][14][15].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a previous study, we reported no adverse effects of CdSe/ZnS QD labeling on the differentiation potential of adult stem cells isolated from rat pancreas [9]. Similar observations for other stem cell types such as embryonic stem cells, induced pluripotent stem cells or mesenchymal ones have recently been published [10][11][12]. Intriguingly, others have noted changes in the differentiation profile of stem cells after labeling with nanoparticles such as the inhibition of osteogenesis with QD labeled bone marrow mesenchymal stem cells [13][14][15].…”
Section: Introductionsupporting
confidence: 78%
“…The major challenge for cell tracking in vitro and in vivo is long-term and non-invasive monitoring of cell migration and differentiation, as well as surveillance of the regenerative potential [1,22,26]. Exceptional and long-lasting fluorescence properties of quantum dot nanocrystals prone them as an excellent tool for labeling cells with the aim of tracking these cells after transplantation [12,27,28]. Prior to an in vivo application, we gained mandatory knowledge of the effects of QDs on the biocompatibility, proliferation and differentiation capabilities of human epithelial stem cells in vitro in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As the persistence of injected MSCs in the joint is limited[14,22,23], their therapeutic effect is likely to be temporary. A single intra-articular injection of MSCs can therefore no longer be considered as an ‘OA treatment for life’ and repeated intra-articular dosing may have more beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…A noninvasive means of imaging and tracking the cell fate after in vivo implantation could be extremely valuable. Quantum dots such as fluorescencelabeled mesoporous silica nanoparticles and superparamagnetic iron oxide (SPIO) nanoparticles have been developed for in vitro and in vivo bioimaging [257,258]. The basic principle for the cell-labeling agents is that enough number of nanoparticles should bind to cells to be detectable.…”
Section: Nanoparticles In Cell Trackingmentioning
confidence: 99%